Multislit diffraction grating spectrometer with mirror lens for imaging spectroscopy - Gulis, Igor M.; Kupreyeu, Alexander G.; Demidov, Ivan D. (Journal of the Belarusian State University. Physics, 2019)
Multislit dispersion spectrometers with the snapshot I(x, y, λ) data cube registration are effectively used for imaging spectroscopy. Using a diffraction grating, instead of a common prism, enables one to increase substantially the number of registered spectral channels. In the present paper we propose the optical design of a multislit dispersion spectrometer with off-axis parabolic mirror lenses. Owing to these mirrors, the optical system becomes simpler and mostly achromatic, possible working spectral range is extended to 0.3-2.0 m. For the mirror lens in the scheme described, the focal distance of a parent parabola is 127 mm, the effective focal distance is 136.12 mm, the working diameter - 50.8 mm, the optical axis deflection angle - 30. As demonstrated by computer simulation using the optical design program, the proposed scheme makes it possible to cover the whole, e. g., visible range (450-750 nm), FWHM in the dispersion direction being no more than 15 m at the resolution limit dλ ≤ 10 nm. The possibility for variations in the dispersion and spectral range by the grating replacement or movement along the optical axis is analyzed.